Composite nanofiber membrane as well as preparation method and application thereof
By depositing a boehmite ceramic layer on the surface of polyimide nanofibers, a composite nanofiber membrane was prepared, which solved the problems of insufficient heat resistance and wettability of polyolefin separators, and realized a high-performance lithium battery separator with excellent mechanical properties and thermal stability.
Patent Information
- Application Number
- CN202410488406.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-23
- Publication Date
- 2025-10-24
AI Technical Summary
Existing polyolefin separators have poor heat resistance and electrolyte wettability, which cannot meet the high energy density requirements of lithium batteries. Polyimide membranes are difficult to polymerize in situ on the surface of polyolefin separators and have insufficient hydrophilicity.
A boehmite ceramic layer of a specific thickness is deposited on the surface of polyimide nanofibers. A composite nanofiber membrane is prepared by electrospinning and heat treatment to form a porous structure to improve wettability. Polyamic acid is generated by the reaction of diamine and diacid anhydride. Combined with the hydrolysis reaction of anhydrous aluminum chloride solution and alkaline solution, a network structure is formed to enhance mechanical strength.
The prepared composite nanofiber membrane has excellent mechanical properties, thermal stability and electrolyte wettability. The process is simple and energy-saving. The thicker boehm ceramic layer improves the overall performance of the composite nanofiber membrane.
Smart Images

Figure CN120830182A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of nanofiber membranes, and particularly relates to a composite nanofiber membrane and a preparation method and application thereof. BACKGROUND
[0002] With the rapid development of 3C products and electric vehicles, the requirement for the energy density of lithium batteries is higher and higher, thus the safety performance of battery explosion and fire is more and more obvious. The heat resistance and the electrolyte wettability of the polyolefin separator on the market are relatively poor.
[0003] Polyimide has the characteristics of high strength, high heat resistance and low density, and can meet the heat resistance requirement of the current market lithium battery. Most of the polyimide is prepared by a two-step method at a high temperature of 300 DEG C. The polyolefin separator cannot withstand the high temperature of 300 DEG C, thus the polyimide cannot be in-situ polymerized on the surface of the polyolefin separator to form a polyimide film. In addition, the hydrophilicity of the polyimide itself is insufficient, and the electrolyte wettability still needs to be improved.
[0004] Therefore, it is urgent to develop a composite nanofiber membrane with good wettability and heat stability. SUMMARY
[0005] In view of the deficiencies of the prior art, the present application aims to provide a composite nanofiber membrane and a preparation method and application thereof. The composite nanofiber membrane has excellent mechanical properties, heat stability and wettability.
[0006] To achieve the object of the present application, the following technical solutions are adopted:
[0007] In a first aspect, the present application provides a composite nanofiber membrane, which comprises composite nanofibers, and the composite nanofibers comprise polyimide nanofibers and a boehmite ceramic layer coated on the surface of the polyimide nanofibers. The thickness of the boehmite ceramic layer is 150-500 nm, for example, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm or 450 nm, etc.
[0008] In the present application, the composite nanofiber membrane is formed by depositing a boehmite ceramic layer with a specific thickness on the surface of the polyimide nanofiber, so that the composite nanofiber membrane has excellent mechanical properties, heat stability and electrolyte wettability.
[0009] Preferably, the diameter of the polyimide nanofiber is 50-800 nm, for example, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm or 700 nm, etc.
[0010] In the present application, the diameter of the polyimide nanofiber is 50-800 nm. When the diameter of the polyimide nanofiber is > 800 nm, the porosity of the composite nanofiber membrane prepared is too large, resulting in defects in the mechanical properties and heat resistance of the composite nanofiber membrane itself. If the diameter of the polyimide nanofiber is < 50 nm, the porosity of the composite nanofiber membrane is too small due to the compactness, and the air permeability is poor.
[0011] Preferably, the boehmite in the boehmite ceramic layer is in a spherical structure or a flaky structure.
[0012] Preferably, the porosity of the composite nanofiber membrane is 30%-65% (e.g., 35%, 40%, 45%, 50%, 55%, or 60%, etc.).
[0013] It should be noted that the thickness of the composite nanofiber membrane is not particularly limited in the present application, and those skilled in the art can adjust it according to the actual situation. The thickness of the composite nanofiber membrane is preferably 11-13 μm, such as 11.2 μm, 11.4 μm, 11.6 μm, 11.8 μm, 12 μm, 12.2 μm, 12.4 μm, 12.6 μm, or 12.8 μm, etc. Of course, in other possible embodiments, the thickness of the composite nanofiber membrane can also be less than 11 μm, such as 7 μm, 8 μm, or 9 μm, etc.
[0014] In a second aspect, the present application provides a preparation method of the composite nanofiber membrane according to the first aspect, which comprises the following steps:
[0015] (1) mixing a diamine, a diacid anhydride, and a solvent, and reacting to obtain a polyamic acid solution;
[0016] (2) electrospinning the polyamic acid solution prepared in step (1), and heat curing to obtain a partially imidized polyimide nanofiber membrane;
[0017] (3) mixing the partially imidized polyimide nanofiber membrane prepared in step (2) and an anhydrous aluminum chloride solution, and reacting, mixing with an alkali solution to hydrolyze, and heat treating to obtain the composite nanofiber membrane;
[0018] The degree of imidization of the partially imidized polyimide nanofiber membrane is 50%-74%, such as 53%, 56%, 59%, 62%, 65%, 68%, or 71%, etc.
[0019] In the present application, the diamine and the dianhydride in step (1) are reacted to form polyamic acid, the carboxyl functional groups in the partially imidized polyimide nanofiber membrane in step (2) are obtained from the polyamic acid, the surface of the partially imidized polyimide nanofiber membrane contains carboxyl (-COOH) and amide (-CONH) functional groups, and step (3) mixes the partially imidized polyimide nanofiber membrane with anhydrous aluminum chloride solution, the Al 3+ The carboxyl groups in the partially imidized polyimide nanofiber membrane are coordinated and reacted, then hydrolysis is performed in an alkaline solution, and finally water and part of the acid radicals generated by the hydrolysis reaction are removed by heat treatment, the partially imidized polyimide nanofiber membrane is converted into a fully imidized polyimide nanofiber membrane, and the composite nanofiber membrane is obtained. During the coordination reaction, the partially imidized polyimide nanofiber membrane is decomposed by the slightly acidic anhydrous aluminum chloride solution and in the alkaline solution, which causes micro-crosslinking between the polyimide nanofibers, forms a network structure, and increases the mechanical strength of the composite nanofiber membrane.
[0020] In the present application, the diamine and the dianhydride in step (1) are reacted to form polyamic acid, the carboxyl functional groups in the partially imidized polyimide nanofiber membrane in step (2) are obtained from the polyamic acid, the surface of the partially imidized polyimide nanofiber membrane contains carboxyl (-COOH) and amide (-CONH) functional groups, and step (3) mixes the partially imidized polyimide nanofiber membrane with anhydrous aluminum chloride solution, the Al
[0021] Preferably, the diamine includes any one or a combination of at least two of 4,4-diaminodiphenyl ether, 3,5-dimethylthio-toluenediamine, diethyl toluene diamine, or 4,4'-methylene-bis(3-chloro-2,6-diethyl aniline).
[0022] Preferably, the dianhydride includes any one or a combination of at least two of pyromellitic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 4,4'-diphthalic anhydride, or 3,3',4,4'-benzophenonetetracarboxylic dianhydride.
[0023] In the present application, the reaction formula of the reaction of the 4,4-diaminodiphenyl ether and the pyromellitic dianhydride to form polyamic acid is shown in formula 1 as follows.
[0024]
[0025] Preferably, the solvent includes any one or a combination of at least two of N,N-dimethylformamide, dimethyl sulfoxide, N-methyl pyrrolidone, or methylamine.
[0026] Preferably, the molar ratio of the diamine and the dianhydride is 1:1-1.2:1.
[0027] Preferably, the mass ratio of the diamine and the solvent is 1:10-1:20.
[0028] Preferably, the temperature of the reaction in step (1) is -10-0℃ (for example, -9℃, -8℃, -7℃, -6℃, -5℃, -4℃, -3℃, -2℃ or -1℃, etc.), and the reaction time is 8-10h (for example, 7.2h, 7.4h, 7.6h, 7.8h, 8h, 8.2h, 8.4h, 8.6h or 8.8h, etc.).
[0029] In the present application, the polyamic acid generated from the dianhydride and the diamine is an exothermic reversible chemical reaction, in which a large amount of isoimide is also generated. The isoimide has low thermal stability and high reactive chemical activity, and the surface of the generated isoimide contains carboxyl functional groups, which is beneficial to the coordination reaction with aluminum chloride in the later stage.
[0030] Preferably, the solid content of the polyamic acid in the polyamic acid solution is 13%-15%, for example, 13.2%, 13.4%, 13.6%, 13.8%, 14%, 14.2%, 14.4%, 14.6% or 14.8%, etc.
[0031] In the present application, the solid content of the polyamic acid in the polyamic acid solution is preferably 13-15%. If the solid content of the polyamic acid in the polyamic acid solution is too low, the viscosity of the polyamic acid solution is relatively small, and the thixotropy is small, which is not conducive to film formation.
[0032] Preferably, the temperature of the thermal curing in step (2) is 200-220℃ (for example, 202℃, 204℃, 206℃, 208℃, 210℃, 212℃, 214℃, 216℃ or 218℃, etc.), and the thermal curing time is 2.0-3.0h (for example, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h or 2.9h, etc.).
[0033] In the present application, the partially imidized polyimide nanofiber membrane is prepared by selecting medium-low temperature (200-220℃) heat curing, thereby retaining the carboxyl group of polyamide acid, greatly simplifying the operation degree of the process, saving energy, and achieving the purpose of reducing cost and increasing efficiency. If the temperature of heat curing is too high, the imidization degree of the prepared partially imidized polyimide nanofiber membrane is relatively high, and the carboxyl functional groups generated on the surface of the polyamide acid are relatively few (due to the gradual ring closure), so that the coordination reaction degree of aluminum ions in aluminum chloride is limited, the thickness of the boehmite ceramic layer generated in the later stage is limited, thereby affecting the related performance; if the temperature of heat curing is too low, the imidization degree of the prepared partially imidized polyimide nanofiber membrane is relatively low, and due to the relatively low temperature, the partially imidized polyimide nanofiber membrane is unstable. Although the content of the surface carboxyl functional groups is relatively high, when the temperature is relatively low, other hybrid functional groups (hydroxyl, carbonyl, etc.) are also generated on the surface, which will consume aluminum ions, so that the coordination reaction degree of aluminum ions in aluminum chloride is limited, the thickness of the boehmite ceramic layer generated in the later stage is limited, thereby affecting the related performance.
[0034] In the present application, the carboxyl vibration peak in infrared spectrum is selected as the standard for testing the imidization degree, the amide group vibration peak is used as the comparison peak, and the completely imidized polyimide nanofiber membrane is used as the standard sample, and the calculation formula of the imidization degree (ID) of the partially imidized polyimide nanofiber membrane is as follows:
[0035]
[0036] Among them, S -COOH is the carboxyl vibration peak absorption light intensity in the partially imidized polyimide nanofiber membrane, S -CONH is the amide group vibration peak absorption light intensity in the partially imidized polyimide nanofiber membrane, S' -COOH is the carboxyl vibration peak absorption light intensity in the completely imidized polyimide nanofiber membrane, and S' -CONH is the amide group vibration peak absorption light intensity in the completely imidized polyimide nanofiber membrane.
[0037] In the present application, the temperature of heat curing in the step (2) is 350℃, and the heat curing time is 2.0h, so as to obtain the polyimide nanofiber membrane.
[0038] Preferably, the solvent of the anhydrous aluminum chloride solution comprises one or more of acetone, ethanol, propylene glycol or ethylene glycol ether, or a combination of any one or at least two thereof.
[0039] Preferably, the concentration of the anhydrous aluminum chloride solution is 0.3-0.8 mol / L, such as 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L, 0.55 mol / L, 0.6 mol / L, 0.65 mol / L, 0.7 mol / L or 0.75 mol / L, and further preferably 0.4-0.8 mol / L.
[0040] In the present application, the concentration of the anhydrous aluminum chloride solution affects the thickness of the boehmite ceramic layer, and as the concentration of the anhydrous aluminum chloride solution increases, the content of the partially imidized polyimide nanofiber membrane surface adsorbed Al 3+ is also increased, and the coordination reaction is more complete, and the thickness of the boehmite ceramic layer in the prepared composite nanofiber membrane is greater, and the performance of the prepared composite nanofiber membrane is better.
[0041] Preferably, the temperature of the reaction in step (3) is 60-80℃, such as 62℃, 64℃, 66℃, 68℃, 70℃, 72℃, 74℃, 76℃ or 78℃, and the reaction time is 1.0-3.0 h, such as 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2.0 h, 2.2 h, 2.4 h, 2.6 h or 2.8 h.
[0042] In the present application, the reaction time of step (3) and the concentration of the anhydrous aluminum chloride solution can affect the crystallinity of the boehmite ceramic layer and the thickness of the boehmite ceramic layer, and the reaction time is 1.0-3.0 h, and the performance of the prepared composite nanofiber membrane is better.
[0043] Preferably, the alkaline solution comprises ammonia.
[0044] Preferably, the concentration of the ammonia is 0.03-0.05 mol / L, such as 0.032 mol / L, 0.034 mol / L, 0.036 mol / L, 0.038 mol / L, 0.040 mol / L, 0.042 mol / L, 0.044 mol / L, 0.046 mol / L or 0.048 mol / L.
[0045] Preferably, the temperature of the hydrolysis is 80-100℃ (82℃, 84℃, 86℃, 88℃, 90℃, 92℃, 94℃, 96℃ or 98℃), and the hydrolysis time is 2.0-6.0 h (such as 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h or 5.5 h).
[0046] In the present application, when the temperature of the hydrolysis is 80-100℃, an increase in temperature can accelerate the breaking of the alicyclic and molecular chain in the hydrolysis reaction, thereby accelerating the hydrolysis speed of the polyimide, and if the temperature of the hydrolysis is lower than 80℃, the hydrolysis effect is poor.
[0047] Preferably, the temperature of the heat treatment is 280-350℃ (for example 285℃, 290℃, 295℃, 300℃, 305℃, 310℃, 315℃, 320℃, 325℃, 330℃, 335℃, 340℃ or 345℃, etc.), and the time of the heat treatment is 1.0-3.0h (for example 1.2h, 1.4h, 1.6h, 1.8h, 2.0h, 2.2h, 2.4h, 2.6h or 2.8h, etc.).
[0048] In the present application, when the temperature of the heat treatment exceeds 280℃, the higher the temperature, the faster the removal of water molecules, the realization of ring closure, and the generation of polyimide.
[0049] In a third aspect, the present application provides a battery separator, which comprises the composite nanofiber film according to the first aspect.
[0050] Compared with the prior art, the present application has the following beneficial effects:
[0051] The composite nanofiber film according to the present application comprises composite nanofibers, which comprise polyimide nanofibers and a boehmite ceramic layer coated on the surface of the polyimide nanofibers. The surface of the boehmite ceramic layer has many polar functional groups, and has good affinity to electrolyte. The boehmite ceramic layer deposited on the surface of the polyimide nanofibers forms a pore structure, which is beneficial to the absorption of electrolyte and has good wettability. The composite nanofiber film also has excellent mechanical properties and thermal stability. The preparation method of the composite nanofiber film has the advantages of simple process, energy saving, cost reduction and efficiency increase, and the thickness of the boehmite ceramic layer in the prepared composite nanofiber is thicker. BRIEF DESCRIPTION OF DRAWINGS
[0052] Figure 1 The infrared spectrograms of pyromellitic dianhydride, 4,4-diamino diphenyl ether and polyamic acid provided for Example 1 are shown in the following figures:
[0053] Figure 2 The infrared spectrograms of the process of gradually cyclizing polyamic acid into polyimide are shown in the following figures:
[0054] Figure 3 The SEM images of the surface of the composite nanofiber provided for Example 1 are shown in the following figures:
[0055] Figure 4 The SEM images of the cross section of the composite nanofiber provided for Example 1 are shown in the following figures:
[0056] Figure 5 The structural schematic diagram of the composite nanofiber provided for Example 1 is shown in the following figure:
[0057] 1-polyimide nanofiber; 2-boehmite ceramic layer. DETAILED DESCRIPTION
[0058] The technical solutions of the present application are further illustrated below by means of specific embodiments. Those skilled in the art should understand that the embodiments are only used to help understand the present application and should not be regarded as specific limitations on the present application.
[0059] Example 1
[0060] The present embodiment provides a composite nanofiber membrane and a preparation method thereof, the composite nanofiber membrane comprising composite nanofibers, the composite nanofibers comprising polyimide nanofibers and a boehmite ceramic layer coated on the surface of the polyimide nanofibers, the thickness of the boehmite ceramic layer being 250 nm, the diameter of the polyimide nanofibers being 100 nm, the boehmite in the boehmite ceramic layer being in a spherical structure, the porosity of the composite nanofiber membrane being 48%, and the thickness of the composite nanofiber membrane being 12 μm.
[0061] The preparation method of the composite nanofiber membrane is as follows:
[0062] (1) 500 g of 4,4-diamino diphenyl ether, 544.6 g of pyromellitic dianhydride and 6500 g of solvent are mixed, reacted at a temperature of 0°C for 9.0 h to obtain a polyamic acid solution, and the solid content of the polyamic acid in the polyamic acid solution is 13.9%;
[0063] (2) The polyamic acid solution prepared in step (1) is electrospun into a polyamic acid membrane using a stainless steel needle with an inner diameter of 1.0 mm as a spinneret, and the electrospinning is operated at a voltage of 20 KV. The polyamic acid membrane is placed in a high-temperature furnace for heat curing, the heat curing temperature is 200°C, and the heat curing time is 2.0 h to obtain a partially imidized polyimide nanofiber membrane, and the imidization degree is 50%.
[0064] (3) The partially imidized polyimide nanofiber membrane prepared in step (2) is immersed in a 0.4 mol / L anhydrous aluminum chloride solution (solvent: acetone) and mixed at 60°C for 1 h, then hydrolyzed in a 0.04 mol / L ammonia solution, the hydrolysis temperature is 90°C, the hydrolysis time is 4 h, and finally placed in a 300°C heat furnace for heat treatment for 2 h to obtain the composite nanofiber membrane.
[0065] Example 2
[0066] The embodiment provides a composite nanofiber membrane and a preparation method thereof, the composite nanofiber membrane comprises composite nanofibers, the composite nanofibers comprise polyimide nanofibers and a boehmite ceramic layer coated on surfaces of the polyimide nanofibers, the boehmite ceramic layer has a thickness of 265 nm, the polyimide nanofibers have a diameter of 100 nm, boehmite in the boehmite ceramic layer is in a spherical structure, the composite nanofiber membrane has a porosity of 47%, and the composite nanofiber membrane has a thickness of 11 microns.
[0067] The preparation method of the composite nanofiber membrane is as follows:
[0068] (1) 500g of 4,4-diamino diphenyl ether, 544.6g of pyromellitic dianhydride and 7000g of a solvent are mixed, reacted, the reaction temperature is -10 DEG C, the reaction time is 10h, and a polyamic acid solution is obtained, wherein the solid content of the polyamic acid in the polyamic acid solution is 13%.
[0069] (2) The polyamic acid solution prepared in step (1) is electrospun into a polyamic acid membrane by using a stainless steel needle with an inner diameter of 1.0mm as a spinneret, the electrospinning is operated under a voltage of 20KV, the polyamic acid membrane is placed in a high-temperature furnace for heat curing, the heat curing temperature is 200 DEG C, the heat curing time is 2.5h, and a partially imidized polyimide nanofiber membrane is obtained, wherein the imidization degree is 55%.
[0070] (3) The partially imidized polyimide nanofiber membrane prepared in step (2) is immersed in a concentrated anhydrous aluminum chloride solution (the solvent is acetone) with a concentration of 0.4mol / L, mixed and reacted at 60 DEG C for 1h, then hydrolyzed in an ammonia water solution with a concentration of 0.03mol / L, the hydrolysis temperature is 100 DEG C, the hydrolysis time is 2h, and finally placed in a 300 DEG C furnace for heat treatment for 2h, so that the composite nanofiber membrane is obtained.
[0071] Embodiment 3
[0072] The embodiment provides a composite nanofiber membrane and a preparation method thereof, the composite nanofiber membrane comprises composite nanofibers, the composite nanofibers comprise polyimide nanofibers and a boehmite ceramic layer coated on surfaces of the polyimide nanofibers, the boehmite ceramic layer has a thickness of 280 nm, the polyimide nanofibers have a diameter of 800 nm, boehmite in the boehmite ceramic layer is in a spherical structure, the composite nanofiber membrane has a porosity of 46%, and the composite nanofiber membrane has a thickness of 13 microns.
[0073] The preparation method of the composite nanofiber membrane is as follows:
[0074] (1) 500 g of 4,4-diaminodiphenyl ether, 544.6 g of pyromellitic dianhydride, and 5900 g of a solvent were mixed, reacted at a reaction temperature of 0°C for 8 h to obtain a polyamic acid solution having a solid content of 15% of polyamic acid in the polyamic acid solution;
[0075] (2) The polyamic acid solution obtained in step (1) was electrospun using a stainless steel needle having an inner diameter of 1.0 mm as a spinneret at a voltage of 20 KV to obtain a polyamic acid membrane, which was heat cured in a high-temperature furnace at a temperature of 200°C for 3.0 h to obtain a partially imidized polyimide nanofiber membrane having an imidization degree of 60%.
[0076] (3) The partially imidized polyimide nanofiber membrane obtained in step (2) was mixed with anhydrous aluminum chloride solution (solvent: acetone) having a concentration of 0.4 mol / L, reacted at 60°C for 1 h, then hydrolyzed in an ammonia solution having a concentration of 0.05 mol / L at a temperature of 80°C for 6 h, and finally heat-treated at 300°C for 2 h to obtain the composite nanofiber membrane.
[0077] Example 4
[0078] The present example provides a composite nanofiber membrane and a method for preparing the same, which are different from those of Example 1 only in that the heat curing temperature in step (2) is adjusted to 210°C, and the partially imidized polyimide nanofiber membrane obtained has an imidization degree of 60%; the composite nanofiber membrane obtained has a boehmite ceramic layer having a thickness of 280 nm, and a porosity of 46%, and the other aspects are the same as those of Example 1.
[0079] Example 5
[0080] The present example provides a composite nanofiber membrane and a method for preparing the same, which are different from those of Example 1 only in that the heat curing temperature in step (2) is adjusted to 220°C, and the partially imidized polyimide nanofiber membrane obtained has an imidization degree of 74%; the composite nanofiber membrane obtained has a boehmite ceramic layer having a thickness of 300 nm, and a porosity of 45%, and the other aspects are the same as those of Example 1.
[0081] Example 6
[0082] The present example provides a composite nanofiber membrane and a method for preparing the same, which are different from those of Example 1 only in that the concentration of the anhydrous aluminum chloride solution (solvent: acetone) in step (3) is adjusted to 0.3 mol / L;
[0083] The boehmite ceramic layer in the prepared composite nanofiber membrane has a thickness of 150 nm, the porosity of the composite nanofiber membrane is 50%, and the other conditions are the same as in Example 1.
[0084] Example 7
[0085] This example provides a composite nanofiber membrane and a preparation method thereof, which are different from Example 1 only in that the concentration of the anhydrous aluminum chloride solution (solvent: acetone) in step (3) is adjusted to 0.5 mol / L.
[0086] The boehmite ceramic layer in the prepared composite nanofiber membrane has a thickness of 300 nm, the porosity of the composite nanofiber membrane is 45%, and the other conditions are the same as in Example 1.
[0087] Example 8
[0088] This example provides a composite nanofiber membrane and a preparation method thereof, which are different from Example 1 only in that the concentration of the anhydrous aluminum chloride solution (solvent: acetone) in step (3) is adjusted to 0.8 mol / L.
[0089] The boehmite ceramic layer in the prepared composite nanofiber membrane has a thickness of 500 nm, the porosity of the composite nanofiber membrane is 42%, and the other conditions are the same as in Example 1.
[0090] This example provides a composite nanofiber membrane and a preparation method thereof, which are different from Example 1 only in that the mass of pyromellitic dianhydride in step (1) is adjusted to 453.83 g, and the molar mass ratio of the binary amine to the binary anhydride is changed to 1.2:1; the boehmite ceramic layer in the prepared composite nanofiber membrane has a thickness of 250 nm, the porosity of the composite nanofiber membrane is 48%, and the other conditions are the same as in Example 1.
[0091] Comparative Example 1
[0092] This comparative example provides a polyethylene diaphragm with a porosity of 45±5% and a thickness of 11 μm, and the manufacturer is Xingyuan Material Technology Co., Ltd., and the brand is SW811G.
[0093] Comparative Example 2
[0094] This comparative example provides a polyethylene boehmite composite diaphragm and a preparation method thereof, and the preparation method of the polyethylene boehmite composite diaphragm is as follows:
[0095] (1) Preparation of boehmite slurry: First, the AlOOH dispersion liquid (Shandong Guocui, HBO-100E) and deionized water were premixed, the premixing time was 2 h, and the rotation speed was 1100 rpm to form a mixed solution (wherein the solid content of the AlOOH slurry was 28%); then water-soluble acrylic glue (brand AS-84, manufacturer Xinyuanbang) was added, the amount of addition was 4wt% of the total mass of the boehmite slurry, the premixing time was 2 h, and the rotation speed was between 1100 rpm; finally, a wetting dispersant (the wetting dispersant was alkyl phenol polyoxyethylene ether, the amount of addition was 0.4wt% of the total mass of the boehmite slurry) was added to the AlOOH slurry, the premixing time was 1 h, and the rotation speed was 700 rpm to obtain the boehmite slurry.
[0096] (2) The boehmite slurry prepared in step (1) was micro-embossed roll coated on a polyethylene separator (porosity 45±5%, thickness 11 μm, manufacturer: Xingyuan Material Technology Co., Ltd., brand: SW512H) to form a polyethylene boehmite composite separator with a thickness of 12 μm.
[0097] Comparative Example 3
[0098] The present comparative example provides a polyimide nanofiber membrane and a preparation method thereof, the preparation method of the polyimide nanofiber membrane is as follows: 500g of 4,4-diamino diphenyl ether and 544.6g of pyromellitic dianhydride are dissolved in 9400g of N,N-dimethylformamide solvent, reacted, the reaction temperature is 320℃, the reaction time is 3h, to obtain a polyamide acid solution, the solid content of polyamide acid in the polyamide acid solution is 10%, the polyamide acid solution is loaded into a 20mL syringe, a stainless steel needle with an inner diameter of 1.0mm is used as a spinneret, an electrospinning technology is applied to prepare a polyimide acid nanofiber membrane, the prepared polyimide acid nanofiber membrane is placed in a hot furnace at 300℃ for 2h to obtain the polyimide nanofiber membrane, the thickness is 12μm.
[0099] Comparative Example 4
[0100] The present comparative example provides a composite nanofiber membrane and a preparation method thereof, the preparation method of the composite nanofiber membrane is as follows:
[0101] (1) 500g of 4,4-diamino diphenyl ether, 544.6g of pyromellitic dianhydride and 9400g of solvent are mixed, reacted, the reaction temperature is 320℃, the reaction time is 3h, to obtain a polyamide acid solution, the solid content of polyamide acid in the polyamide acid solution is 10%; the polyamide acid solution is loaded into a 20mL syringe, a stainless steel needle with an inner diameter of 1.0mm is used as a spinneret, an electrospinning technology is applied to prepare a polyimide acid nanofiber membrane, the prepared polyimide acid nanofiber membrane is placed in a hot furnace at 300℃ for 2h to obtain a polyimide nanofiber membrane;
[0102] (2) The polyimide nanofiber membrane is placed in a potassium hydroxide solution (2 mol / L) for 2 min, taken out, ultrasonically cleaned for 5 min, and then placed in an acetic acid solution (5% by mass) for 1 h, taken out, and ultrasonically cleaned for 30 min to obtain a polyimide nanofiber membrane containing a carboxyl active functional group on the surface; the polyimide nanofiber membrane containing a carboxyl active functional group on the surface is immersed in an aqueous ammonia solution (0.04 mol / L) for 1 h, taken out, and ultrasonically cleaned for 30 min to obtain a polyimide nanofiber membrane with a surface quaternary ammonium group; and then the polyimide nanofiber membrane with a surface quaternary ammonium group is placed in an anhydrous aluminum chloride solution (0.4 mol / L, solvent: acetone) at 60°C for 1 h, and then hydrolyzed in an aqueous ammonia solution with a concentration of 0.04 mol / L, the hydrolysis temperature being 90°C and the hydrolysis time being 4 h, and the treated membrane is placed in a 300°C furnace for 2 h to obtain the composite nanofiber membrane.
[0103] The composite nanofiber membrane comprises composite nanofibers, the composite nanofibers comprise polyimide nanofibers and a boehmite ceramic layer coated on the surface of the polyimide nanofibers, the thickness of the boehmite ceramic layer is 60 nm, the diameter of the polyimide nanofibers is 100 nm, the boehmite in the boehmite ceramic layer is in a spherical structure, the porosity of the composite nanofiber membrane is 65%, and the thickness of the composite nanofiber membrane is 12 μm.
[0104] Comparative Example 5
[0105] This comparative example provides a composite nanofiber membrane and a preparation method thereof, which are different from those of Example 1 only in that the concentration of the anhydrous aluminum chloride solution (solvent: acetone) in step (3) is adjusted to 0.15 mol / L.
[0106] The thickness of the boehmite ceramic layer in the prepared composite nanofiber membrane is 80 nm, and the porosity of the composite nanofiber membrane is 55%. The other conditions are the same as those in Example 1.
[0107] Comparative Example 6
[0108] This comparative example provides a composite nanofiber membrane and a preparation method thereof, which are different from those of Example 1 only in that the temperature of thermal curing in step (2) is adjusted to 225°C, and the degree of imidization of the prepared partially imidized polyimide nanofiber membrane is 80%; the thickness of the boehmite ceramic layer in the prepared composite nanofiber membrane is 130 nm, and the porosity of the composite nanofiber membrane is 53%. The other conditions are the same as those in Example 1.
[0109] The composite nanofiber membranes, polyethylene separators, polyethylene-boehmite composite separators, and polyimide nanofiber membranes provided in the above examples and comparative examples were tested, and the specific testing methods are as follows.
[0110] Mechanical properties: The tensile strength was tested according to GB / T1040[1].3-2006, the tensile rate was 200 mm / min, and the testing direction was the membrane longitudinal direction (MD).
[0111] Thermal stability: The composite nanofiber membranes, polyethylene separators, polyethylene-boehmite composite separators, and polyimide nanofiber membranes provided in the examples and comparative examples were baked at 250°C for 1 hour and at 320°C for 1 hour, respectively, as the baking conditions, and the thermal shrinkage rate of the membrane longitudinal direction (MD) and the membrane transverse direction (TD) was tested.
[0112] Wetting performance: The contact angle of the composite nanofiber membranes, polyethylene separators, polyethylene-boehmite composite separators, and polyimide nanofiber membranes provided in the examples and comparative examples to an electrolyte was tested, and the electrolyte included the following components by mass percentage: solvent (ethylene carbonate) 30 wt%, lithium salt (lithium hexafluorophosphate) 50 wt%, and additive (vinylene carbonate) 20 wt%.
[0113] The test results are shown in Table 1.
[0114] Table 1
[0115]
[0116]
[0117] In Table 1, " / " represents that the test was not performed.
[0118] As can be seen from the content of Table 1, the composite nanofiber membranes provided in Examples 1-9 have a tensile strength ≥ 45.2 MPa, an MD thermal shrinkage rate at 320°C / H ≤ 2.5%, a TD thermal shrinkage rate at 320°C / H ≤ 2.8%, and a contact angle ≤ 10.5°, and have excellent mechanical properties, thermal stability, and wettability.
[0119] From the test results of Example 1, Example 6, Example 7, Example 8 and Comparative Example 5, it can be seen that as the concentration of the anhydrous aluminum chloride solution increases, the contact angle of the prepared composite nanofiber membrane decreases, and the wettability is improved better. When the concentration of the anhydrous aluminum chloride solution is 0.3 mol / L (Example 6), the contact angle decreases compared with Comparative Example 5. When the concentration of the anhydrous aluminum chloride solution reaches 0.4 mol / L and above, the contact angle decreases to a limited extent with the increase of the concentration of the anhydrous aluminum chloride solution, and the wettability improvement ability is limited. With the increase of the concentration of the anhydrous aluminum chloride solution, the number of active functional groups on the surface of the composite nanofiber membrane increases, which leads to the increase of the adsorption complex efficiency and the thickness of the boehmite ceramic layer formed, and the corresponding thermal shrinkage rate is relatively reduced. In summary, the thicker the boehmite ceramic layer, the lower the corresponding thermal shrinkage rate (baked at 250°C for 1 hour, baked at 320°C for 1 hour), the better the wettability (the lower the contact angle), and the smaller the porosity.
[0120] The thermal curing temperature and time determine the imidization degree of the polyimide. When the thermal curing temperature is higher (200-220°C) and the time is longer (2-3h), the imidization degree is more obvious. The partially imidized polyimide film is decomposed in the anhydrous aluminum chloride acetone and dilute ammonia water solution with partial acidity, causing micro-crosslinking between the fibers (forming a network structure in terms of spatial form), resulting in the increase of the mechanical strength, and the corresponding tensile strength increases. From the test results of Example 1, Example 4 and Example 5, it can be seen that when the imidization degree increases from 50% to 74%, the corresponding tensile strength increases from 45.2 MPa to 78.5 MPa, showing a proportional relationship. However, compared with Example 1, if the thermal curing temperature in step (2) is too high (Comparative Example 6), the imidization degree of the partially imidized polyimide nanofiber membrane is 80%. When the imidization degree is higher, the carboxyl functional groups generated on the surface of the polyamic acid are less (due to the gradual ring closure), and therefore the coordination reaction degree of the aluminum ions in the aluminum chloride is limited, the thickness of the boehmite ceramic layer prepared is thin, thereby affecting the related performance, and the thermal stability and wettability decrease. Therefore, it is known that by controlling the thermal curing temperature in step (2), the imidization degree of the partially imidized polyimide nanofiber membrane is within a certain range, and the performance of the prepared composite nanofiber membrane is better.
[0121] The electrolyte wettability of the diaphragm is a key performance of the lithium ion diaphragm, because it directly affects the lithium ion transmission performance and the important index of electrolyte penetration. The electrolyte absorption rate can be measured by comparing the wetting area of the electrolyte, but it cannot be shown with data, so the contact angle characteristics are used to show the difference between the wettability. As can be seen from the comparison of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, the size of the contact angle is: Comparative Example 1 (polyethylene diaphragm) > Comparative Example 3 (polyimide nanofiber membrane) > Comparative Example 4 (composite nanofiber membrane) > Comparative Example 2 (polyethylene boehmite composite diaphragm) > Example 1 (composite nanofiber membrane), because the polyethylene diaphragm itself has a non-polar surface and a low surface energy characteristic, so it is the worst in wettability. Compared with the polyethylene diaphragm, the polyimide nanofiber membrane itself also has a low surface energy characteristic, but the material itself has a rich functional group, so the wettability is also relatively better than the polyethylene diaphragm. Due to the limitation of the preparation process, the composite nanofiber membrane provided by Comparative Example 4 has a limited thickness of the boehmite ceramic layer prepared, and the wettability is lower than that of the composite nanofiber membrane provided by Example 1. The polyethylene boehmite composite diaphragm and the composite nanofiber membrane provided by Example 1 perform best in wettability, because the surfaces of both are covered with inorganic ceramic boehmite, and the boehmite surface has many polar functional groups, which have very good affinity for electrolyte. Another reason is that the surface is covered with boehmite, forming a pore structure, which is beneficial to the absorption of electrolyte. Therefore, the composite nanofiber membrane provided by the present application has excellent wettability for electrolyte.
[0122] The thermal stability is an important index for measuring the safety performance of the battery. It can be known from the comparison of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 that the thermal stability is in the order of: Example 1 (composite nanofiber membrane) > Comparative Example 4 (composite nanofiber membrane) > Comparative Example 3 (polyimide nanofiber membrane) > Comparative Example 2 (polyethylene boehmite composite separator) > Comparative Example 1 (polyethylene separator). The polyethylene separator and the polyethylene boehmite composite separator (within a certain coating amount range) cannot withstand 180 DEG C, because the melting point of polyethylene itself is relatively low, and the microporous structure is destroyed beyond a certain temperature, and even melts. The melting point temperature of polyimide itself is relatively high, up to 280 DEG C, and when greater than 300 DEG C, the shrinkage of the polyimide nanofiber membrane greatly increases, and the heat resistance becomes poor. After modification, the thermal shrinkage performance of the composite nanofiber membrane (Example 1) at a high temperature of 320 DEG C / H is better than that of the comparative examples. This is related to the boehmite ceramic layer formed by the composite nanofiber membrane. Boehmite is a super-high temperature resistant material, and due to the particularity of the structure of the composite nanofiber membrane (the boehmite ceramic layer is equivalent to the protective shell of the polyimide nanofiber), the heat resistance is greatly improved. The thermal stability of the composite nanofiber membrane provided by Comparative Example 4 is relatively low, because the traditional process is to open the ring by alkaline hydrolysis, and the carboxyl functional groups generated on the surface of the polyimide nanofiber membrane by weak acid are low in concentration, the thickness of the boehmite ceramic layer formed is small, and the thermal stability is relatively low. Therefore, the composite nanofiber membrane provided by the present application has high heat resistance.
[0123] It can be known from the comparison of Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 that the tensile strength is in the order of: Example 1 (composite nanofiber membrane) > Comparative Example 4 (composite nanofiber membrane) > Comparative Example 3 (polyimide nanofiber membrane) > Comparative Example 2 (polyethylene boehmite composite separator). This is because the mechanical properties of polyimide material are greater than those of polyolefin material. The reason why the mechanical properties of the composite nanofiber membrane provided by Example 1 are far superior to those of the polyimide nanofiber membrane is that, in the coordination reaction process, part of the imidized polyimide nanofiber membrane is decomposed in the acidic anhydrous aluminum chloride solution and ammonia water, causing micro-crosslinking between the polyimide nanofibers (forming a similar network structure from the spatial form), resulting in an increase in mechanical strength. It can be known from the comparison of Example 1, 6-8 that, as the concentration of anhydrous aluminum chloride solution increases, the micro-crosslinking reaction will be more intense, and the mechanical properties will be further improved. The mechanical properties of the composite nanofiber membrane provided by Comparative Example 4 are lower than those of the composite nanofiber membrane provided by Example 1, mainly because the imide bond will be broken to produce the corresponding amide ion and nucleophilic ion (decomposed into small molecular substances) during the ring-opening reaction of the closed-ring polyimide in the preparation method of Comparative Example 4, resulting in a decrease in tensile strength.
[0124] From the comparison between Example 1 and Comparative Example 4, it can be seen that the composite nanofiber membrane prepared in Example 1 has high tensile strength, low thermal shrinkage, low contact angle and better performance. The reason is that: Comparative Example 4 adopts a high temperature (300°C) ring-closure reaction to form polyimide, and then an alkaline hydrolysis ring-opening reaction will produce side reactions, resulting in poor stability of the polyimide itself and reduced strength. The reason is that polyimide is prone to hydrolysis reaction in a strong alkaline environment, and the phenylene and imide bonds will change respectively. Among them, the phenylene will undergo an oxidation reaction to form phenylene or phenol. The imide bond will break to produce corresponding amide ions and nucleophilic ions (rearrangement and exchange reactions will occur to form small molecule products), and the loose matrix will cause internal defects in the material. The polyimide nanofiber membrane after ring opening is acidified with a weak acid (acetic acid) to prepare a carboxyl functional group. (The acid concentration cannot be too high, as polyimide will also undergo hydrolysis reaction when encountering strong acid. However, the low concentration of weak acid limits the carboxyl functional groups obtained). The limited concentration of carboxyl groups in the inorganic material (boehmite) formed by the coordination complex reaction will result in a low thickness of the boehmite ceramic layer. Therefore, it has a certain impact on the wettability, tensile strength and thermal shrinkage properties of the composite nanofiber membrane.
[0125] In Example 1, polyamic acid is synthesized by diamine and dibasic acid anhydride, and a partially imidized polyimide nanofiber membrane is obtained by thermal curing. The partially imidized polyimide nanofiber membrane retains the carboxyl functional group and does not need to undergo ring opening and acidification reaction. Therefore, the generation of secondary side reactions and the decrease in stability are avoided, and a thicker boehmite ceramic layer than in the prior art can be prepared, which has a more significant improvement in wettability and mechanical strength. The partially imidized polyimide nanofiber membrane is prepared by selecting medium and low temperature (200°C) thermal curing, thereby retaining the carboxyl group of the polyamic acid. Therefore, the operation of the process is greatly simplified, energy is saved, and the purpose of reducing costs and increasing efficiency is achieved.
[0126] Figure 1 The infrared spectra of pyromellitic dianhydride (a in the figure), 4,4-diaminodiphenyl ether (b in the figure) and polyamic acid (c in the figure) provided in Example 1 are as follows: after pyromellitic dianhydride and 4,4-diaminodiphenyl ether react to form polyamic acid under certain process conditions, Figure 1 As shown in the figure, the bands a and b of pyromellitic dianhydride and 4,4-diaminodiphenyl ether disappear, and the band at 1660 cm -1 The amide I band representing the amide group (i.e., the carbonyl stretching peak vibration in the amide group) is located at 1545 cm -1 Represents the amide I band (i.e., the NH angle vibration and CN stretching vibration in the amide group, at 1726 cm -1 The C=O stretching vibration of the carboxyl group and the wavelengths between 2500 and 3100 cm -1The OH stretching vibration of the hydrogen bond produces the spectrum band c of polyamic acid.
[0127] The polyamic acid film obtained in step (2) of Example 1 was heat-cured in a high-temperature furnace at 180°C to 350°C. The temperatures of the high-temperature furnace were 180°C, 200°C, 210°C, 220°C, 250°C, 300°C, 330°C and 350°C, respectively. The heat curing time was 2.0 h. A series of partially imidized polyimide nanofiber membranes were obtained and subjected to infrared spectroscopy testing. Figure 2 The infrared spectrum of the process of polyamic acid gradually cyclizing to polyimide. It can be clearly seen from the figure that as the temperature rises, the first 1660cm -1 (carbonyl stretching peak vibration in amide group), 1545cm -1 (NH angle vibration and CN stretching vibration in amide group) and 1726cm -1 (representing the C=O stretching vibration in the carboxyl group) and other absorption peaks, among which 1545 cm -1 The NH angular vibration and CN stretching vibration in the amide group are very sensitive to temperature (between 200 and 250°C), and show a significant downward trend as the temperature rises. However, the amide and carboxyl peaks will gradually decrease (the degree of decrease gradually slows down) as the imidization process is completed (the temperature reaches 300°C to 350°C). Therefore, it can be seen that controlling the temperature of the thermal curing in step (2) within the range of 200 to 220°C can partially imidize the polyamic acid to form a polyimide and maximize the amount of carboxyl groups in the polyamic acid.
[0128] In order to calculate the degree of imidization, the imidization degree of the partially imidized polyimide nanofiber membrane was calculated as follows, using 1726 cm -1 The carboxyl vibration peak at 1545 cm was used as the standard for testing the degree of imidization (ID). -1 The vibration peak of the amide group at the position is used as a comparison peak, and a fully imidized polyimide (a polyimide nanofiber membrane prepared by heat curing a polyamic acid membrane at 350°C for 2.0h) is used as a standard sample. The imidization degree (ID1) of the partially imidized polyimide nanofiber membrane in Example 1 is calculated as follows: ID1 (%) = (S 1726,200℃,2.0h / S 1545,200℃,2.0h ) / (S' 1726,350℃,2.0h / S' 1545,350℃,2.0h ).
[0129] Among them, S 1726,200℃,2.0h 、S 1545,200℃,2.0h The thermal curing temperature is 200℃, the thermal curing time is 2.0h, and the prepared partially imidized polyimide nanofiber membrane has a thermal conductivity of 1726cm -1 1545cm -1S' 1726,350℃,2.0h , S' 1545,350℃,2.0h represent the absorption light intensity of the partially imidized polyimide nanofiber membrane prepared at a heat curing temperature of 350℃ and a heat curing time of 2.0h at 1726cm -1 , 1545cm -1 .
[0130] At a heat curing temperature of 200℃, the corresponding absorbance at 1726cm -1 is 1.2, and the absorbance at 1545cm -1 is 0.8; at 350℃, the corresponding absorbance at 1726cm -1 is 0.6, and the absorbance at 1545cm -1 is 0.2. It is calculated that the imidization degree of the partially imidized polyimide nanofiber membrane at a heat curing temperature of 200℃ is 50.0%.
[0131] The imidization degree (ID5) of the partially imidized polyimide nanofiber membrane in Example 5 is calculated according to the following formula: ID5 (%) = (S 1726,220℃,2.0h / S 1545,T=220℃,2.0h ) / (S' 1726,T=350℃,2.0h / S' 1545,T=350℃,2.0h ).
[0132] wherein, S 1726,220℃,2.0h , S 1545,220℃,2.0h represent the absorption light intensity of the partially imidized polyimide nanofiber membrane prepared at a heat curing temperature of 220℃ and a heat curing time of 2.0h at 1726cm -1 , 1545cm -1 . S' 1726,350℃,2.0h , S' 1545,350℃,2.0h represent the absorption light intensity of the partially imidized polyimide nanofiber membrane prepared at a heat curing temperature of 350℃ and a heat curing time of 2.0h at 1726cm -1 , 1545cm -1 .
[0133] At a heat curing temperature of 220℃, the corresponding absorbance at 1726cm -1 is 1.0, and the absorbance at 1545cm -1 is 0.45; at 350℃, the corresponding absorbance at 1726cm -1 is 0.6, and the absorbance at 1545cm -1The absorbance of the sample was 0.2. It was calculated that the imidization degree of the partially imidized polyimide nanofiber membrane was 74.0% at the heat curing temperature of 220℃. It can be seen that the heat curing temperature is 200-220℃, and the imidization degree of the prepared partially imidized polyimide nanofiber membrane is 50%-74.0%.
[0134] Figure 3 The SEM image of the composite nanofiber surface provided for Example 1 clearly shows that boehmite has wrapped the polyimide nanofiber surface to present a linear shell structure, and there is no free state. Figure 4 The SEM image of the cross section of the composite nanofiber provided for Example 1 clearly shows that there is a circle of boehmite (white in the figure) around the polyimide nanofiber, clearly reflecting the structure of polyimide nanofiber as the core and boehmite as the shell, proving that boehmite is deposited on the surface of the polyimide nanofiber, Figure 5 The schematic diagram of the structure of the composite nanofiber.
[0135] The applicant declares that the process method of the present application is illustrated by the above examples, but the present application is not limited to the above process steps, that is, it does not mean that the present application must rely on the above process steps to be implemented. It should be understood by those skilled in the art that any improvement on the present application, equivalent replacement of the raw materials selected by the present application, addition of auxiliary ingredients, selection of specific methods, etc. fall within the protection scope and disclosure scope of the present application.
Claims
1. A composite nanofiber membrane, characterized by, The composite nanofiber membrane comprises composite nanofibers, the composite nanofibers comprise polyimide nanofibers and a boehmite ceramic layer coated on the surface of the polyimide nanofibers, and the thickness of the boehmite ceramic layer is 150-500 nm.
2. The composite nanofiber membrane according to claim 1, wherein, The diameter of the polyimide nanofiber is 50-800 nm.
3. The composite nanofiber membrane according to claim 1 or 2, characterized in that, The porosity of the composite nanofiber membrane is 30%-65%.
4. A method for preparing the composite nanofiber membrane according to any one of claims 1 to 3, characterized by, The preparation method comprises the following steps: (1) mixing a diamine, a dianhydride and a solvent, and reacting to obtain a polyamic acid solution; (2) electrospinning the polyamic acid solution prepared in step (1), and heat curing to obtain a partially imidized polyimide nanofiber membrane; (3) mixing the partially imidized polyimide nanofiber membrane prepared in step (2) and an anhydrous aluminum chloride solution, and reacting, mixing with an alkali solution to hydrolyze, and heat treating to obtain the composite nanofiber membrane; The degree of imidization of the partially imidized polyimide nanofiber membrane is 50%-74%.
5. The preparation method according to claim 4, characterized in that The diamine comprises any one or a combination of at least two of 4,4-diamino diphenyl ether, 3,5-dimethylthio toluene diamine, diethyl toluene diamine or 4,4'-methylene-bis(3-chloro-2,6-diethyl aniline); Preferably, the dianhydride comprises any one or a combination of at least two of pyromellitic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 4,4'-diphthalic anhydride or 3,3',4,4'-benzophenonetetracarboxylic dianhydride; Preferably, the solvent comprises any one or a combination of at least two of N,N-dimethylformamide, dimethyl sulfoxide, N-methyl pyrrolidone or methylamine; Preferably, the molar ratio of the diamine and the dianhydride is 1:1-1.2:1; Preferably, the mass ratio of the diamine and the solvent is 1:10-1:
20.
6. The production method according to claim 4 or 5, characterized by, The temperature of the reaction in step (1) is -10-0 ℃, and the reaction time is 8-10 h; Preferably, the solid content of the polyamic acid in the polyamic acid solution is 13%-15%.
7. The method of any one of claims 4-6, wherein, The temperature of the heat curing in step (2) is 200-220 ℃, and the heat curing time is 2.0-3.0 h.
8. The method of any one of claims 4-7, wherein, The solvent of the anhydrous aluminum chloride solution comprises any one or a combination of at least two of acetone, ethanol, propylene glycol or glycol ether; Preferably, the concentration of the anhydrous aluminum chloride solution is 0.3-0.8 mol / L; Preferably, the temperature of the reaction in step (3) is 60-80 ℃, and the reaction time is 1.0-3.0 h.
9. The method of any one of claims 4-8, wherein, The alkali solution comprises ammonia water; Preferably, the concentration of the ammonia water is 0.03-0.05 mol / L; Preferably, the temperature of the hydrolysis is 80-100 ℃, and the hydrolysis time is 2-6 h; Preferably, the temperature of the heat treatment is 280-350 ℃, and the heat treatment time is 1.5-3.0 h.
10. A battery separator characterized by, The battery separator comprises the composite nanofiber membrane according to any one of claims 1-3.